Experimental Study on Directional Shear of Q2 Remolded Loess Considering the Direction of Principal Stress - Wang, Sui; Zhao, Peng; Gao, Zhihua; Zhong, Zuliang; Chen, Bin; Wu, Bo; Sun, Qingjun; Song, Chunxia (Frontiers in Earth Science, 2022)
To investigate the strength and deformation characteristics of Q2 remodeled loess, soil samples from the Lishi area in Shanxi Province were adopted to examine the effects arising from the principal stress axis direction angle α and the medium principal stress ratio b on the shear and non-coaxial properties of remodeled loess based on the hollow cylindrical torsional shear system. As indicated by this study, when b was constant, the generalized shear stress ratio decreased with the increase in α at 0°–45°, while achieving the minimum value when α = 45°; α increased again with the increase in the principal stress axis direction angle at 45°–90°. When α was 0–45°, the generalized shear stress ratio tended to decrease with the increase in the intermediate principal stress ratio b. When α was 60°–90°, the shear strength ratios at different intermediate principal stress ratios were obtained as: strength at b = 0.5 > strength at b = 1 > strength at b = 0. Moreover, after the degree of strength volatility of this remodeled loess was defined to determine its breaking strain standard, it was found through a comparative analysis that when the generalized shear strain of this remodeled loess was 6.5%, the strength of this remodeled loess was over 90%. Thus, this study suggested the use of its generalized shear strain of 6.5% as its breaking strain standard. In addition, when α was at 0–45°, the direction angle of strain increment increased with the increase in the direction angle of the principal stress axis and reached the peak at 45°. When α was at 60°–90°, the direction angle of strain increment decreased with the increase in the direction angle of the principal stress axis, i.e., the non-coaxial characteristics of the remolded loess first increased, then decreased, and further tended to be coaxial.